PROBLEMATICS OF THE DEVELOPMENT OF SHARIA MUTUAL FUNDS IN INDONESIA - Muhammad Sodiki; Parman Komarudin; Mahmud Yusuf; Hendera Hadi; Imro Atut Toyyibah (Badamai Law Journal, 2022)
ABSTRACTThe development of the capital market in Indonesia has become a special attraction for investors to invest in the stock exchange. However, to be able to invest directly, there are several obstacles faced by investors such as limited knowledge, information and time. One alternative investment instrument that can be a solution to these problems is mutual funds. The development of Islamic mutual funds in Indonesia has indeed been under pressure in the past year. This is reflected in the decline in the managed funds of Islamic mutual funds which appear to decline at the end of 2021 and tend to be flat until the first quarter of 2022 to March 2022. The purpose of this research is to analyze the problems in the development of Islamic mutual funds in Indonesia. In this study using the method of literature (library research) with a qualitative approach. The results of the study show that the obstacles to developing Islamic mutual funds are caused by several factors, including: lack of literacy about mutual funds, dualism that occurs in the capital market, the need for assistance from stakeholders to work together. Another factor that can cause mutual funds to decline is inflation, causing the purchasing power of public money in general to decrease.